THE ROLE OF MONETARY POLICY IN CONTROLLING INFLATION RATES IN LIGHT OF THE DECLINE IN THE VALUE OF THE IRAQI DINAR - Muaamal Hussein Jwesim (Journal Park Publishing, 2024)
Inflation represents a fundamental problem in various developing and developed countries, as it negatively affects all macro variables of the economy, as these countries always seek to control its rates within moderate limits with which the economy can coexist and develop. In this aspect, the monetary administration in Iraq sought independence by... Law 56 of 2004, and its use of modern monetary tools as a currency selling window, is one of the primary and most appropriate methods in achieving stability in the general level of prices by achieving stability in the exchange rate of the local currency, especially in light of the economic conditions prevailing in the Iraqi economy, but the problem lies in its own recent decisions. By adjusting the value of the local currency towards the dollar, which created a state of increasing price levels, it came once again to use its tools to control it. The research concluded that the monetary policy followed by the Central Bank with its various tools contributed significantly to improving the currency's value and reducing inflation rates in the country.
Keywords: Monetary policy, inflation, exchange rate, monetary policy and its effect on inflation.